Elite participation in the Third Crusade - Bennett, Stephen ca. 20./21. Jh (The Boydell Press, 2021)
The motivations behind those who went on the Third Crusade examined through close investigation of their social networks
Title from publisher's bibliographic system (viewed on 04 Mar 2021)
Keywords: Sozialgeschichte; Crusades / Third, 1189-1192; Upper class families / England / History / To 1500; Nobility / England / History / To 1500; Kreuzzug -- 1189-1192; Elite; Verzeichnis